O "Partido partido": a cobertura da crise política do PT e do Governo Lula em 2005 na pauta de Teoria e Debate - Araújo, Erilene (2008)
The magazine Teoria e Debate (TD) is the most traditional communication vehicle of the Worker s Party (PT). It was created in 1987 by the Regional Directorate of the PT in São Paulo and, since 1997 has been published by the Fundação Perseu Abramo, also an organ of the party. The magazine is produced with the voluntary collaboration of intellectuals and organized by a small editorial staff. The objective of the magazine is to go beyond the limits of the partisan media and to be perceived as a space for debate and reflection about Brazilian leftist theories. When the magazine had gained some maturity, TD was faced with a big challenge: how to discuss the political crisis of 2005, which had touched the center of the PT and President Luiz Inácio Lula da Silva s government. The present dissertation studies these questions: How did the political crisis of 2005 which was known as the mensalão case enter into the contents of Teoria e Debate? What was said and which individuals were chosen to narrate the case? The research was done by analysis of 38 political articles published in the magazine in 2005 and 2006. As it is an analytical publication elaborated by and addressed to intellectuals, the first chapter of the dissertation relates theoretical reflections about the intellectuals and their politics, utilizing ideas from classic authors such as Antonio Gramsci and Daniel Pécaut. The second chapter discusses the genesis of the Worker s Party analyses and the intellectual participation in the process of its creation and then discusses the loss of political influence of the group since the 1990 s, when the electoral campaigning created a new dimension in the PT. The third chapter is dedicated an analysis of party communication and the impact of that communication during the crises of 2005 caused mainly by the magazine. Based on the analysis of the 38 articles, the last chapter discusses the Teoria e Debate coverage in three periods: before, during and after the political crises of 2005